Tribološke lastnosti jekla nitriranega v plazmi in prekritega z DLC-prevleko - Podgornik, Bojan (Materiali in tehnologije, 2000)
Samples made of AISI 4140 steel were surface treated by plasma nitriding and coated with a hydrogen-free hard-carbon coating. The specimens were investigated in terms of their microhardness, residual stress, coating adhesion and dry-sliding wear resistance. Wear tests in which duplex-treated specimens were mated to hardened ball-bearing steel were performed under unidirectional and reciprocating sliding. To examine the influence of the nitriding conditions on the performance of duplex-treated steel, the coating was deposited on hardened as well as on plasma-nitrides samples, nitrided under two different nitriding conditions. The results show a greatly improved sliding wear resistance of the plasma-nitrided hard-coated specimens compared with un-coated and pre-hardened specimens, for both unidirectional and reciprocating sliding. Furthermore, a hydrogen-free hard-carbon coating produced a reduction in the coefficient of friction of about one order of magnitude. Although previous investigations showed a negative effect of the compound layer, it was found that this layer may act as an intermediate hard layer, leading to superior tribological properties of the composite.
Keywords: tribološke lastnosti; jekla; nitriranje v plazmi; drsenje; obraba